Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1016/j.neurobiolaging.2012.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of extracellular signal-regulated kinase 1/2 activity by calmodulin KII modulates p21Cip1 levels and survival of immortalized lymphocytes from Alzheimer’s disease patients

Abstract: Previously, we reported a Ca(2+)/calmodulin (CaM)-dependent impairment of apoptosis induced by serum deprivation in Alzheimer's disease (AD) lymphoblasts. These cell lines showed downregulation of extracellular signal-regulated kinase (ERK)1/2 activity and elevated content of p21 compared with control cells. The aim of this study was to delineate the molecular mechanism underlying the distinct regulation of p21 content in AD cells. Quantitative reverse transcription polymerase chain reaction analysis demonstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 67 publications
1
18
0
Order By: Relevance
“…In SAD lymphocytes an impaired progression of the G1/S phase occurs, consistent with p21's main change and its known function in arresting G1 [17]. Experiments with serum withdrawal also exhibited elevation of p21 level in the cytosol and changes of E2F and NF-κB transcription factors' activity [56]. The reduced NF-κB activation in AD cells seems to protect them from death induced by the loss of trophic factors.…”
Section: Dysregulated Cell Cycle In Lymphocytessupporting
confidence: 63%
“…In SAD lymphocytes an impaired progression of the G1/S phase occurs, consistent with p21's main change and its known function in arresting G1 [17]. Experiments with serum withdrawal also exhibited elevation of p21 level in the cytosol and changes of E2F and NF-κB transcription factors' activity [56]. The reduced NF-κB activation in AD cells seems to protect them from death induced by the loss of trophic factors.…”
Section: Dysregulated Cell Cycle In Lymphocytessupporting
confidence: 63%
“…In contrast, significant downregulation of MDM2 has also been observed in some diseases. For example, MDM2 expression is downregulated in AD, AKI, DN, and DCM . All of these changes in the expression of MDM2 may be considered as a potential biomarker for the diagnosis of these diseases.…”
Section: General Discussion and Future Research Directionsmentioning
confidence: 99%
“…Recent studies have indicated that MDM2 also contributes to the pathogenesis of AD via p53‐independent mechanisms (Figure ). Esteras et al have shown that MDM2 is downregulated in the lymphoblasts from AD patients compared with control lymphoblasts. MDM2 downregulation in AD may lead to FOXO3a stabilization, which in turn increases p21 transcription and promotes the pathogenesis of AD …”
Section: Roles Of Mdm2 In Dementia and Neurodegenerative Diseasesmentioning
confidence: 99%
“…The higher CaM content was associated with impaired cell survival/death mechanisms [15,36]. Since cell cycle dysfunction seems to be a convergent point in neurodegenerative diseases [37], it was interesting to determine whether the control failure of CaM levels was commonly involved in neurodegenerative processes or, otherwise, was a disease-specific marker.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the CaM content appears to regulate the rate of p27 degradation in AD cells through a phosphoinositide-3 kinase/Akt-dependent mechanism [15]. Moreover, higher levels of CaM also correlated with the resistance of AD cells to serum deprivation-induced apoptosis [36]. CaM thus seems to play a pivotal role in transmitting proliferative/survival signals from the plasma membrane to the nucleus.…”
Section: Discussionmentioning
confidence: 99%